Role of HbA1c with mortality and severity among the patients of Acute coronary syndrome: a prospective study - Chandel, Satish; Parihar, Shishirendu; Gramani, Bharat; Dubey, T. N. (International Journal of Advances in Medicine, 2019)
Background: Blockage of coronary artery lead to a reduction of blood flow towards heart resulting in Coronary Artery Disease (CAD). CAD leads to myocardial complications. CAD is one of the important causes of death all over the world including India. Diabetes mellitus is a risk factor for CAD. Reports have also shown to increase in cardiovascular morbidity among patients with glucose intolerance. In present study we tried to find the relationship of HbA1c levels with mortality, morbidity, and severity in Acute Coronary Syndrome (ACS). Methods: Two hundred patients with ACS were studied from 2018 to 2019 at Gandhi Medical College and Hamidia Hospital, Bhopal. Following a thorough medical history routine medical examination including laboratory investigations was performed in all the patients. Electrocardiography (ECG), creatine phosphokinase-muscle/brain (CPK-MB), echocardiography and coronary angiography (CAG) was also done as part of this study. Results: Mean age of the study cohort was 59.17±8.75 years. Out of 200 subjects, 110 (55%) were non-diabetic, 52 (26%) were diabetic, 38 (19%) had weakened glucose tolerance and 82 (41%) had hypertension. Left ventricular dysfunction (LVD) and heart failure (HF) were the common complications and were more prevalent among diabetic patients than the nondiabetics (p=0.009). HbA1c level (7.01±2.23) was high among subjects with complications than the subjects without complications (6.01±1.36). Conclusions: The patients with DM have higher morbidity and mortality than the non-diabetic patients of ACS and therefore such patients should be screened for diabetes and glucose intolerance for better management of CAD.